"On water" synthesis of highly functionalized 4H-chromenes via carbon–carbon bond formation under microwave irradiation and their antibacterial properties. Issue 37 (24th March 2015) - Rao, L. Chandrasekhara; Kumar, N. Satish; Dileepkumar, V.; Murthy, U. S. N.; Meshram, H. M.
Abstract : Microwave assisted synthesis catalyst-free synthesis water as a solvent anti bacterial properties. Abstract : An ecofriendly and catalyst free synthesis of novel hybrid molecules of chromene and coumarin is described by C–C bond formation in an aqueous medium under microwave irradiation. The methodology provides cleaner conversion, a shorter reaction time and high regio selectivity which makes the protocol globally recognized. For the first time the reaction between a special type of allylic alcohols 2-hydroxy-2 H -chromens and 4-hydroxy coumarin to produce novel functionalised 4 H -chromenes in excellent yields was achieved and we evaluated their antibacterial properties.